2022
DOI: 10.1038/s41417-021-00418-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of CAR T-cell for acute lymphoblastic leukemia (ALL) treatment: a review study

Abstract: Acute lymphoblastic leukemia (ALL) is a cancer-specific lymphoid cell. Induction and consolidation chemotherapy alone or in combination with different therapeutic approaches remain the main treatment. Although complete or partial remission of the disease can be achieved, the risk of relapse or refractory leukemia is still high. More effective and safe therapy options are yet unmet needs. In recent years’ new therapeutic approaches have been widely used. Hematopoietic Stem Cell Transplantation (HSCT) presents s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 168 publications
(269 reference statements)
0
59
0
1
Order By: Relevance
“…While overall 5-year survival rates for leukemia remain high, treatment of relapsed leukemia remains a major obstacle as these patients often present with chemoresistance and a significantly impaired immune system [17,18]. CAR-T cell therapies have been explored for use in leukemia and have shown some success in recognition of cancer cells, but this form of treatment is often coupled with severe side effects including encephalopathy, coagulopathy, hypoxia, and neurotoxicity [19][20][21][22]. With the success of targeting the immune system for improved patient recovery, less toxic alternatives to CAR-T therapies are being actively explored.…”
Section: Leukemiamentioning
confidence: 99%
“…While overall 5-year survival rates for leukemia remain high, treatment of relapsed leukemia remains a major obstacle as these patients often present with chemoresistance and a significantly impaired immune system [17,18]. CAR-T cell therapies have been explored for use in leukemia and have shown some success in recognition of cancer cells, but this form of treatment is often coupled with severe side effects including encephalopathy, coagulopathy, hypoxia, and neurotoxicity [19][20][21][22]. With the success of targeting the immune system for improved patient recovery, less toxic alternatives to CAR-T therapies are being actively explored.…”
Section: Leukemiamentioning
confidence: 99%
“…CAR T-cell success is exemplified by FDA-approval of the anti-CD19 CAR T-cell tisagenelcleucel for treatment of acute lymphoblastic leukemia (ALL) and axicabtagene ciloleucel for diffuse large B-cell lymphoma (DLBCL). In early 2021, liso-cel received FDA-approval for DLBCL, based upon significant efficacy and low toxicity ( 45 , 46 ).…”
Section: Mechanisms Of Resistance To Car T-cell Therapymentioning
confidence: 99%
“…CAR T-cell success is exemplified by FDA-approval of the anti-CD19 CAR T-cell tisagenelcleucel for treatment of acute lymphoblastic leukemia (ALL) and axicabtagene ciloleucel for diffuse large B-cell lymphoma (DLBCL). In early 2021, liso-cel received FDA-approval for DLBCL, based upon significant efficacy and low toxicity (45,46). CAR can be directed to the TRAC locus, resulting in uniform CAR expression, reduced tonic signaling, decreased exhaustion and increased antitumor efficacy and gives the added benefit of producing a potential universal product.…”
Section: Mechanisms Of Resistance To Car T-cell Therapymentioning
confidence: 99%
“…Clinical trials conducted on patients with acute lymphocytic leukemia have shown a complete recovery in up to 92% of patients with very meaningful results ( 20 ). CAR-T cell therapy is being actively implemented for treating large B-cell lymphoma and B-cell precursor acute lymphoblastic leukemia ( 22 , 23 ). Although this CAR-T cell therapy has achieved clinical success in some hematologic cancer patients ( 24 ), it has two main problems that need improvement.…”
Section: Introductionmentioning
confidence: 99%